3D-Dynamic Modelling and Performance Analysis of Service Behavior for Beam Pumping Unit. (12th July 2018) - Zi-Ming, Feng; Jing-Jing, Tan; Yanan, Sun; De-Shi, Zhang; Wei-Bo, Duan
Abstract : In consideration of the rod, the tube, and the liquid column, a 3D dynamic model was established, which could be expressed as a set of partial differential equations. A measured torque curve and a calculated torque curve of Nan1-2-22 oil-well in Daqing oilfield were contrasted with each other which improved the rationality of this model. At last, we researched the influence of the stroke and the frequency of stroke on the displacement of rod, suspension velocity, suspension acceleration, polish rod load, and net torque of gearbox. This 3D dynamic model has a higher calculated accuracy and veracity and could be used to design and optimize the structure of rod pumping and the working process of pumping wells.